The Isolated States of America: Home State Bias and the Impact of State Borders on Mobility - Riley Wilson (Center for Economic Studies and ifo Institute (CESifo), 2023)
I document a new fact about mobility within the United States. County-to-county migration and commuting drop discretely at state borders. People are three times as likely to move to a county 15 miles away, but in the same state, than to an equally-distant county across state lines. Standard economic explanations, like differences in amenities or moving costs, have little explanatory power. Experimental evidence suggests many people experience "home state bias" and discount out-of-state moves, independent of whether social ties are present. This pattern has real economic costs, resulting in local labor markets that are less dynamic after negative economic shocks.
Keywords: J61; R23; D91; 330; internal migration; commuting; social networks; home state bias; border discontinuities